2018
DOI: 10.1186/s12889-018-5681-5
|View full text |Cite
|
Sign up to set email alerts
|

Missed treatment opportunities and barriers to comprehensive treatment for sexual violence survivors in Kenya: a mixed methods study

Abstract: BackgroundIn Kenya, most sexual violence survivors either do not access healthcare, access healthcare late or do not complete treatment. To design interventions that ensure optimal healthcare for survivors, it is important to understand the characteristics of those who do and do not access healthcare. In this paper, we aim to: compare the characteristics of survivors who present for healthcare to those of survivors reporting violence on national surveys; understand the healthcare services provided to survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Most providers, and especially the students, were unclear about their ethical and legal responsibilities to these victims. This lack of training may be a regional problem as evidenced in studies from other parts of sub-Saharan Africa, 11,12,33,43 and elsewhere. 15,36,44,45 Across Africa, providers need training in how to treat both rape and IPV victims, when and how to refer, and the procedures in the collection and handling of forensic evidence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most providers, and especially the students, were unclear about their ethical and legal responsibilities to these victims. This lack of training may be a regional problem as evidenced in studies from other parts of sub-Saharan Africa, 11,12,33,43 and elsewhere. 15,36,44,45 Across Africa, providers need training in how to treat both rape and IPV victims, when and how to refer, and the procedures in the collection and handling of forensic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…21 In our case study, some experienced providers appeared unaware about the availability of rape kits, collection procedures including sample contamination, and its transportation. Studies in other parts of Africa have also reported poor healthcare provider knowledge of forensic evidence protocols including evidence collection 11,12,15,33,43 and a shortage of specialized units for rape victims with reference to studies done in Kenya, Ghana and South Africa. 11,46,47 These units act as "one stop centers" in managing assault survivors in a holistic approach, catering for victims' physical and mental health as well as judicial and welfare needs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations